Beneficiation of Gold Bearing Ores Associated with the Tertiary Volcanism in South Sardinia (Italy) - S. di Giovanni; G. Zonnedda; M. Ghiani; A. Serci; R. Peretti; A. Zucca (International Mineral Processing Congress, 2003)
"Beneficiation of the epithermal gold mineralizations associated with an extensive alteration zone in the Serrenti-Furtei region on the island of Sardinia, is proving a complex issue. Experimental investigations have in fact demonstrated that while the ores contained in the upper parts of the deposit are amenable to conventional cyanidation, the gold contained in the refractory ores in the lower portions needs to be recovered by means of flotation, combined with leaching where necessary.The results of commercial heap leaching, carbon-in-leach (CIL) processing and flotation, designed on the basis of the experimental findings and applied to the oxidized portions and transition zones of the deep sulphide mineralizations, confirmed the expectations emerging from the laboratory tests."